La correspondance de Charles de Galles et de ses proches lors des négociations de mariage à Madrid en 1623 : regards intimes sur la cour d’Espagne - Sabrina Juillet-Garzón (E-Spania)
The visit of Charles of Wales in Madrid in 1623 during the negotiations for his marriage to Infanta Maria was the occasion of a wide diplomatic correspondence between the courts of Spain and the court of James VI & I, based in London. Part of them dealt with the diplomatic evolution whereas others dealt with the daily life of the Prince and his companions at the court of Philip IV. Some of these letters present the reader with an insider look on the adventure of this prince who endeavoured to go and fetch his fiancée despite the opposition of his father the King, crossing three countries in Europe at war. This paper proposes a study of the “intimate” letters between Charles of Wales and his closest companions –George Villiers, Duke of Buckingham, and Endymion Porter with their families in England. It will show an unknown aspect of these negotiations, presenting touching anecdotes and often ignored and surprising faces of Charles and Buckingham, as well as a more intimate perception of Philip IV’s and his Spanish court. It will demonstrate how essential this correspondence was in the evolution of the negotiations by giving a perspective from the inside which will explain the motivations of Charles of Wales and Buckingham to stay in Spain whatever it cost them to conclude the match and then to understand why the latter never happened.